Non-phosgene route for the synthesis of methyl phenyl carbamate using ordered AISBA-15 catalyst - Lucas, Nishita; Amrute, Amol P.; Palraj, K.; Shanbhag, G. V.; Vinu, Ajayan; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
Methyl phenyl carbamate (MPC) has been synthesized Under liquid phase conditions from dimethyl carbonate and aniline by using mesoporous AISBA-15 catalyst. The catalyst with different Si/Al ratio was synthesized by isomorphous Substitution of aluminium into the framework of siliceous SBA-15. The structural integrity of the catalyst system was diagnosed with the help of various characterization techniques Such as X-ray diffraction, Surface analysis, and the acidity measurement has been done by TPD using ammonia as probe molecule. AISBA-15 (Si/Al = 10) exhibited highest catalytic activity in the synthesis of MPC under the reaction Conditions Studied. The effect of parameters Such as molar ratio of reactants, catalyst concentration. reaction temperature and time on the conversion of aniline was investigated. The results demonstrated that an aniline conversion of 99% and MPC selectivity of 71% were achieved when the reaction was carried out at 100 C, DMC to aniline mole ratio of 10 with 5% of catalyst (wt% of total reaction mixture) for 3 h. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: amines; Dimethyl carbonate; Mesoporous AISBA-15; Methoxycarbonylation; Methyl phenyl carbamate

Sol-gel synthesis of MoO(3)/SiO(2) composite for catalytic application in condensation of anisole with paraformaldehyde - Amrute, Amol P.; Bordoloi, Ankur; Lucas, Nishita; Palraj, K.; Halligudi, Shivaraj B. (Catalysis Letters, 2008)
MoO(3)/SiO(2) composite with varying amounts of MoO(3) loading (1-20 wt.%) were prepared by sol-gel method and calcined at 500 C. These catalysts were employed for the liquid phase condensation of anisole with paraformaldehyde. All the catalysts were characterized by N(2) sorption, XRD, and NH(3)-TPD. The activities of synthesized MoO(3)/SiO(2) catalysts were compared with p-toluene sulfonic acid (p-TSA), the most frequently used catalyst for the condensation reactions, and with a supported metal oxide (WO (x) /ZrO(2)). Under the similar reaction conditions, synthesized 10 wt.% MoO(3)/SiO(2) catalyst calcined at 500 C was found to be the most active in the condensation of anisole with paraformaldehyde.
Keywords: 4; 4'-Dimethoxydiphenylmethane; Condensation of anisole; MoO(3)/SiO(2) composites; Paraformaldehyde; Sol-gel synthesis

Titania supported silicotungstic acid: an efficient solid acid catalyst for veratrole acylation - Waghmare, Nilesh G.; Kasinathan, Palraj; Amrute, Amol P.; Lucas, Nishita; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Titania supported silicotungstic acid (STA) with different STA loading (10-25 wt%) and calcination temperature (650-750 degrees C) were prepared by wet impregnation method. The catalysts have been represented by a general formula xSTiO(2)y (where x denotes wt%, S denotes STA and y denotes calcination temperature in degrees C). These catalysts were characterized by techniques such as X-ray diffraction, surface analysis, FTIR-pyridine and TPD-NH(3) and were used as heterogeneous solid acid catalysts in the liquid phase acylation of veratrole with acetic anhydride (Ac(2)O). It was found that 20STiO(2)700 gave the highest activity in acylation reaction due to its highest acidity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acetic anhydride; Acylation; Silicotungstic acid; titania; veratrole

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia

Dehydration of fructose to 5-hydroxymethyl furfural over ordered AlSBA-15 catalysts - Lucas, Nishita; Kokate, Ganesh; Nagpure, Atul; Chilukuri, Satyanarayana V. (Microporous and Mesoporous Materials, 2013)
5-Hydroxymethyl furfural is an important platform chemical. It is successfully synthesized from renewable carbohydrates using mesoporous AlSBA-15 catalysts under biphasic conditions. Fine tuning of the catalyst acidity is important to drive the reaction to give good yields of furan compound. Al-SBA-15 catalysts with different Si/Al ratios were prepared and characterized by XRD, Al-27 MASNMR, SEM, TEM, N-2 sorption, ICP-OES and TPD of ammonia. Results show that part of aluminium is substituted into tetrahedral positions. The catalyst with lower acid site density but medium to strong acid strength favours selective formation of HMF. Under the optimized conditions, HMF selectivity was as high as 88% at 59 mol% conversion of fructose. Leaching of part of aluminium occurs under hydrothermal conditions, if solvent mixtures containing water are used, while activity can be retained if DMSO is used as solvent. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Acidity; AlSBA-15; dehydration; fructose; Hydroxymethyl furfural

Acid-base cooperative catalysis over mesoporous nitrogen-rich carbon - Goyal, Reena; Sarkar, Bipul; Lucas, Nishita; Bordoloi, Ankur (ChemCatChem, 2014)
WOx nanoclusters (2-3 nm) embedded on a mesoporous nitrogen-rich carbon material were synthesized by using novel methodology. This material was very effectively capitalized as a new carbon-based acid-base cooperative catalyst for sequential acetal hydrolysis and Knoevenagel condensation reactions. The protocol was also explored for the nitroaldol condensation reaction.
Keywords: cooperative catalysts; Knoevenagel condensation; mesoporous materials; Nanostructures; nitro aldol reaction

Novel catalysts for valorization of biomass to value-added chemicals and fuels - Lucas, Nishita; Kanna, Narasimha Rao; Nagpure, Atul S.; Kokate, Ganesh; Chilukuri, Satyanarayana V. (Journal of Chemical Sciences, 2014)
Key furan compounds such as 5-hydroxymethylfurfural (HMF), 2,5-furandicarboxylic acid (FDCA) and 2,5-dimethylfuran (DMF) were synthesized from renewable feedstocks. Dehydration of fructose was carried out in biphasic conditions employing several solid acid catalysts by targeting selective formation of HMF. Its selectivity is linearly dependent on total acidity clearly revealing that lower acidity favours selective formation of HMF. Oxidation and hydrogenolysis of HMF has been explored using 2 wt% Ru-K-OMS-2. The catalysts used for each transformation were subjected to detailed characterization using XRD, BET surface area, temperature-programmed desorption and transmission electron microscopy. The effect of various reaction parameters was also investigated for obtaining high yields of desired chemical intermediates. High FDCA yields of 93.4 mol% and 66 mol% were achieved in alkaline and base-free conditions, respectively. The 2 wt% Ru-K-OMS-2 is a versatile catalyst as it also catalyses HMF hydrogenolysis giving 33 mol% of DMF. Thus, utility of various novel materials as catalysts has been demonstrated in the multistep transformations of hexoses to furan-based fuels and chemicals.
Keywords: 2; 5-dimethylfuran; 5-furan dicarboxylic acid; 5-hydroxymethyl furfural; dehydration; fructose

Renewable fuels from biomass-derived compounds: Ru-containing hydrotalcites as catalysts for conversion of HMF to 2,5-dimethylfuran - Nagpure, Atul S.; Venugopal, Ashok Kumar; Lucas, Nishita; Manikandan, Marimuthu; Thirumalaiswamy, Raja; Chilukuri, Satyanarayana V. (Catalysis Science & Technology, 2015)
Production of transportation fuels from renewable biomass is hugely important considering the current ecological concerns over CO2 built up in the atmosphere. Ruthenium-containing hydrotalcite (HT) catalysts were applied for the selective hydrogenolysis of biomass-derived 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF). Structural and morphological features of the catalysts were examined using various physico-chemical characterization techniques. The influence of various reaction parameters, such as reaction temperature, solvent, Ru content of the catalyst, etc., was investigated with respect to HMF conversion and DMF yield. The study clearly shows that well-dispersed Ru nanoparticles are highly active and selective in the conversion of HMF to DMF. A catalyst containing only 0.56 wt% Ru converted 100 mol% HMF to yield 58 mol% DMF. This catalyst was found to be recyclable as the activity was retained even after five cycles of reaction. 2-Propanol was found to be a good solvent as it helped to improve DMF yield through transfer hydrogenation. Based on the results of the investigations, a reaction pathway for the conversion of HMF to DMF was proposed for the present Ru-based catalyst system.

Studies of synergy between metal-support interfaces and selective hydrogenation of HMF to DMF in water - Goyal, Reena; Sarkar, Bipul; Bag, Arijit; Siddiqui, Nazia; Dumbre, Deepa K.; Lucas, Nishita; Bhargava, Suresh Kumar; Bordoloi, Ankur (Journal of Catalysis, 2016)
Metal-support interfaces play a very important role in heterogeneous catalysis. The interfacial interactions not only are responsible for stabilizing the necessary oxidation state to facilitate the reaction but also enhance the stability of the catalyst system. Nano dispersion of Ni on mesoporous nitrogen-rich carbon material has been achieved using two different synthesis methods. It was observed that nickel (0) gets stabilized by strong interfacial interaction with the nitrogen atoms of the support material, and the material was found to be very economic and efficient for the conversion of HMF to DMF in aqueous medium. The material shows >= 99% conversion to 5-(hydroxymethyl) furfural (HMF) within 6 h of reaction with 98.7% DMF selectivity. A unique correlation between synthesis methods and particle sizes with catalytic performance has been observed for these newly developed materials. Furthermore, a DFT calculation has been performed to predict the reaction mechanism. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: biofuels; Biomass; Hydrogenation; mesoporous carbon; Ni-CNx

Heteropolyacids supported on mesoporous AlSBA-15 as efficient catalysts for esterification of levulinic acid - Lucas, Nishita; Gurrala, L.; Athawale, Anjali (Journal of Porous Materials, 2019)
A comparative study of different heteropoly acids supported on mesoporous AlSBA-15 for the synthesis of ethyl levulinate has been undertaken for the first time. The catalysts were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, inductively coupled plasma-optical emission spectrometry, thermo gravimetric analysis, temperature programmed desorption of NH3 and N-2 sorption studies. Insights into crucial parameters for the esterification reactions are also furnished. A distinct correlation was observed between acid density and conversion revealing that the distribution of acidic sites and their accessibility by the reactant moieties plays an important role in determining the overall activity. The effects of various reaction parameters were investigated to enhance the catalytic activity and yield of ethyl levulinate. Under the optimized conditions, levulinic acid conversion of 87.4 mol% and ethyl levulinate selectivity of 100% could be obtained with silicotungstic acid supported on AlSBA-15.

Valorization of oceanic waste biomass: a catalytic perspective - Lucas, Nishita; Athawale, Anjali A.; Rode, Chandrashekhar V. (Chemical Record, 2019)
Efficacious waste utilization is vital in context of sustainability. The past decade has witnessed attempts of usage of land biomass and wastes for various applications, contributing towards a sustainable society. Exploitation of the marine biomass, which does not compete with habitation and food production like land biomass has been largely unnoticed and therefore not being utilized judiciously. Researchers have mainly exploited these resources as functional materials having significant potential applications. However, a catalytic perspective for the valorisation of these polymers arising from oceanic waste widens their scope and ameliorates its use. The objective of the present review is to demonstrate the effectiveness of chitin/chitosan as a catalyst and as a feedstock for deriving important fuels and chemicals. It displays all the reactions heterogeneously catalyzed by them along with the strategic methodology. Their important catalytic organic transformations attempted so far, have also been discussed. The future perspectives are also presented which if inculcated would improve the value addition of the waste, paving a way for greener and imperishable world.

Efficacy of clay catalysts for the dehydration of fructose to 5-hydroxymethyl furfural in biphasic medium - Lucas, Nishita; Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana (Journal of Porous Materials, 2020)
5-Hydroxymethyl furfural (HMF) is one of the important platform chemical obtained from C6 sugars derived from biomass. The efficiency of montmorillonite clay catalysts (K-10, K-20, K-30, and Al pillared clay) has been systematically explored for the synthesis of HMF through dehydration of fructose in a biphasic solvent system. The catalysts were characterized by XRD, N(2)sorption,Al-27 MAS NMR,Si-29 NMR and FT-IR of chemisorbed pyridine. Acid treated K-10 catalyst was found to be the best among the clay catalysts tested. Various reaction parameters such as reaction temperature, catalyst content, solvent were optimized for achieving better yield of HMF. Under optimized reaction conditions, K-10 catalyst affords 80 mol% fructose conversion with HMF yield of 61 mol%. Insight into the type of acid sites essential for such cascade reactions has been furnished. Utilization of clay catalysts for HMF production will be beneficial to improve overall economics for the production of platform chemicals like HMF from biomass-derived raw materials.
Keywords: 5-hydroxymethyl furfural; Acidity; Clays; fructose; Insights

Efficacy of octahedral molecular sieves for green and sustainable catalytic reactions - Lucas, Nishita; Gurrala, Lakshmiprasad; Halligudi, S. B. (Molecular Catalysis, 2020)
Sustainability and Green Chemistry has emerged as catchphrase in modern era and researchers worldwide have embraced it as new paradigm of development. In this context identifying potential materials able to curb multiple grave issues thus contributing towards sustainability is vital. Catalytic materials are quite potent for addressing current social, economic and environmental problems like harnessing alternative energy source, pollution prevention/remediation and manufacturing of commodity chemicals. Thus, the present review accentuates the efficacy of porous octahedral molecular sieves (OMS) as catalyst for such environmentally important reactions. It discusses about structural importance of OMS and their applications for green and sustainable catalytic reactions. Finally, the limitations are highlighted and future perspectives are presented which will ameliorate its catalytic utilization in energy and environmental domains.
Keywords: catalytic transformations; Lignocellulosic biomass; octahedral molecular sieves; platform chemicals; renewable feedstock

Novel Ru nanoparticle catalysts for the catalytic transfer hydrogenation of biomass-derived furanic compounds - Nagpure, Atul S.; Gogoi, Pranjal; Lucas, Nishita; Chilukuri, V. Satyanarayana (Sustainable Energy & Fuels, 2020)
The catalytic transfer hydrogenation (CTH) reaction was investigated for boosting the reduction of biomass-derived furanic compounds to obtain high-quality liquid biofuels. The CTH of 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF) and furfural to 2-methylfuran (MF) was thoroughly studied over the Ru, Pd, Au, Pt, Ni, Rh and Cu metal catalysts supported on nitrogen-doped mesoporous carbons (NMCs) by utilizing 2-propanol as a source of hydrogen. The structural characteristics of the materials were examined by employing various physico-chemical methods, such as XRD, N(2)sorption, CHN analysis, XPS, FT-IR spectroscopy, H-2-TPR, TEM, CO2-TPD, ICP-OES and Raman spectroscopy. The influence of the N content, basicity of the catalyst, reaction temperature, hydrogen donor, nature of the catalyst support and transition metal was systematically investigated with regard to the substrate conversions and product yields. The correlation between the N content (wt%) of the catalysts and the Ru nanoparticle size (nm) and turnover frequency (h(-1)) was also investigated. Highly dispersed Ru nanoparticles (1.9 nm) supported on NMC displayed admirable catalytic performance in CTH for the conversion of HMF to DMF and furfural to MF. The catalyst Ru-NMC with a good N content (11.4 wt%) gave 84 and 87 mol% yields of DMF and MF, respectively, with 2-propanol as the source of hydrogen under mild reaction conditions. In addition, this catalyst demonstrated excellent recyclability. The better catalytic activity of the Ru-NMC catalyst in the CTH of HMF and furfural was credited to the small size of the Ru metal nanoparticles (1.9 nm), high N content, superior metal-support interaction and mesoporous framework of the catalyst.

Direct conversion of N-acetyl-d-glucosamine to N-containing heterocyclic compounds 3-acetamidofuran and 3-acetamido-5-acetyl Furan - Shaikh, Samrin S.; Patil, Chetana R.; Lucas, Nishita; Bokade, Vijay V.; Rode, Chandrashekhar V. (Waste and Biomass Valorization, 2023)
Purpose Effectual waste utilization from plant as well as marine biomass has gained tremendous importance with reference to sustainability. The valorization of marine biomass produces value added compounds containing not only C, H, O but also renewable N atom in the skeleton which widens the scope for its exploration which may prove to be economically beneficial to the society. Heterogeneous catalytic transformation of marine biomass i.e. N-acetyl glucosamine (NAG) to N-substituted aromatic heterocyclic furan derivatives is reported for the very first time. Cost effective and stable metal oxide catalysts were deployed for the transformation. Catalyst screening study showed that La2O3 was found to be an excellent catalyst for N-acetyl glucosamine (NAG) dehydration which mainly produced 3-acetamidofuran (3AF). Methods The physicochemical properties of the metal oxide catalyst were investigated by various techniques such as XRD, FTIR, MeOH-FTIR, TPD, SEM, N-2 sorption studies and HR-TEM analysis for structure activity relationship. Results The effect of various reaction parameters such as catalyst concentration, reaction temperature, reaction time and solvent effect on dehydration of N-acetyl glucosamine has been studied in detail for higher yields. The results revealed that the presence of weak basic sites which are Bronsted in nature and nano pores present on the surface were responsible for improved dehydration of the chitin biomass to selectively yield 3-acetamidofuran (3AF). La2O3 catalyst showed optimum 50% 3AF yield from N-acetyl glucosamine at 180 degrees C in 3 h. Conclusion Efficacious exploitation of marine biomass to value added chemicals using heterogeneous catalysts can be extensively exploited. Separation of N-substituted heterocyclic aromatics is the most innovative aspect of the current study. Thus, utilization of heterogeneous catalyst and renewable biomass as a raw material indicates a transition towards more sustainable and greener approach.{GRAPHICAL ABSTRACT
Keywords: 3-acetamido-5-acetylfuran; 3-acetamidofuran; dehydration; heterogeneous catalysis; Lanthanum oxide; N-acetyl-D-glucosamine; renewable feedstock

Sustainable UV absorbing bio-plastic films by valorisation of humins and chitosan - Lucas, Nishita; Tambe, Snehal S.; Parate, Roopa; Hengne, Amol; Rode, C. V.; Athawale, Anjali A. (International Journal of Biological Macromolecules, 2025)
Humins, an inevitable bio-refinery waste by-product of sugar dehydration have been efficiently utilized for the first time for developing biodegradable thin films for UV shielding. The films were prepared from chitosan, and humins, a novel combination, aiming towards simultaneous utilization of marine and bio-refinery waste, rendering simple, effective, robust UV absorbing films. The structure-activity relationship of these films were elucidated with the help of different analytical techniques like X-ray diffraction, Fourier transform infrared spectroscopy, Thermogravimetric analysis, UV-vis spectroscopy, Atomic force microscopy, Scanning electron microscopy, Tensile testing, Contact angle measurements and water absorption studies. Intrinsic biodegradability was studied using fungi i.e. Aspergillus niger. Different feedstocks (corncob, rice husk, glucose and xylose) were explored for generating humins. Amongst them, humins derived from xylose were utilized for the preparation of the bio-plastic films of chitosan. The results revealed that, addition of 5.0 % humins was observed to be an optimum concentration yielding films with excellent UV absorption, mechanical properties, and biodegradability. The current work is in perfect alignment with sustainability and green chemistry as it ameliorates waste valorization (lignocellulosic and marine altogether). Further, its innovation stems from the first-hand use of humins for UV absorption, novel combination of biopolymers, use of green raw materials.
Keywords: biodegradable; Chitosan; Humins; Thin films; UV absorption; Waste valorization